2017
DOI: 10.3997/1873-0604.2017015
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the sedimentary fabrics in ornamental rocks by using GPR

Abstract: In this study, the use of ground-penetrating radar for characterising ornamental sedimentary rocks was tested. Specifically, the ability of this non-invasive geophysical prospecting method to identify fabrics and textures in rocks was investigated. Blocks mined from quarries were analysed, and ornamental rocks with the same lithologies as other widely utilised ornamental rocks with a variety of sedimentary fabrics and textures were selected. Rocks with clastic brechoid, cross-laminated sparitic, massive or lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The AI-COSTSQO project is focused on, among others, the detection and characterization of discontinuities and fractures of the rock mass, affecting ornamental stone production and, consequently, the generation of waste. Previous work in the scientific literature related to fracture detection based on Ground Penetrating Radar (GPR) measurement can be found in [1][2][3][4][5][6][7][8][9][10][11]. The fracture characterization allowed the development and use of optimization algorithms that can reduce the generation of waste for environmental protection, increase economic revenue, and increase the recovery ratio of the quarries.…”
Section: Discussionmentioning
confidence: 99%
“…The AI-COSTSQO project is focused on, among others, the detection and characterization of discontinuities and fractures of the rock mass, affecting ornamental stone production and, consequently, the generation of waste. Previous work in the scientific literature related to fracture detection based on Ground Penetrating Radar (GPR) measurement can be found in [1][2][3][4][5][6][7][8][9][10][11]. The fracture characterization allowed the development and use of optimization algorithms that can reduce the generation of waste for environmental protection, increase economic revenue, and increase the recovery ratio of the quarries.…”
Section: Discussionmentioning
confidence: 99%
“…Alile et al (2016) carried out experimental approach of twodimensional (2D) geoelectrical resistivity imaging in which the resistivity is allowed to vary both laterally along and vertically beneath the survey line, series of 2D apparent resistivity data were generated and the survey revealed lateritic soil, sand, sandstone, shale, limestone, clay, dolomite with resistivity values ranging between 259 Wm to 2159 Wm. Olaseni and Airen (2021) also did research using 3-D ERT to investigate the type of minerals' deposit that can be found in Ugonoba village and the research revealed that at the depth range between 25 m and 33.7 m, the following were found: sand-clay, lateritic sand, sandstone and limestone with high resistivity values ranging from 6001 Ωm to 14376 Ω m. Depending on the chosen geophysical method, operating any method with GPR can achieve high resolution (a few cm) to a depth of a few metres, as attenuation of the electromagnetic waves is comparably small in highly resistive hard rock environments as claimed by Rey et al (2017) and Elkarmoty et al (2017). Here, we consider another potentially useful geophysical exploration technique, electrical resistivity tomography (ERT).…”
Section: Introductionmentioning
confidence: 86%
“…This includes the use of non-invasive geophysical imaging techniques [5], which have the potential to map subsurface property distributions that are linked to variations in density, porosity, moisture or mineralogy [6]. To-date, the most commonly applied geophysical approach in hard rock exploration is ground penetrating radar (GPR), which employs electromagnetic waves propagating through the rock that are reflected at discontinuities in the electromagnetic properties of the rock, e.g., at fractures or joints [5,[7][8][9][10][11]. Depending on the chosen operating frequency, GPR can achieve high resolution (a few cm) to a depth of a few metres, as attenuation of the electromagnetic waves is comparably small in highly resistive hard rock environments.…”
Section: Introductionmentioning
confidence: 99%